KORELASI GAYA KEPEMIMPINAN KEPALA SEKOLAH DENGAN MOTIVASI KERJA GURU - Moh. Harun Al Rosid; Mukhfidatul Mukarromah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
This study ain to determine the correlation of principal’s leadership style with work motivation of SMK Darussalam Teaschers in Blokagung Tegalsari Banyuwangi 2018/2019 Academic Year. This research was in the from of a quantitative descriptive study, with a population of all members of the teaher council and secondary data. And use the validity test to obtain relevant and accurate data. The data collection techniques in this study used a questionnaire, observation and documentation. By using data analysis techniques, prodect moment. And the last hypothesis testing to test the truth of a statement statistically and draw conclusions. Based on the discussion of the theory and the results of the analysis, discussion and interpretation results as well as some data from the field, the researcher can conclude the following: Based on the results of the questionnaire on variable X dan Y there is a significant correlation between the leadership style of the headmaster and the work motivation of teachers in SMK Darussalam Blokagung Tegalsari Banyuwangi in the 2018/2019 academic year of 0.667. this means that there is a strong relationship.